(untitled) (Povijesni prilozi (Historical Contributions), 2019)
Based on the available documents, the author has analysed the connections between converts to Islam and the Christian part of their families, and the way in which the conversions influenced the lives of converts and their Christian relatives. Adopting another religion did not mean abandoning the old habits and Christian traditions. Regardless of the change of religion and the new religious practices they had to follow, there were those who continued living in accordance with the Christian tradition. The converts’ contacts with their Christian families contributed to that considerably. The diff erence in name and religion did not break family ties even when families were separated.